Alterations in skeletal muscle abundance of protein turnover, stress, and antioxidant proteins during the periparturient period in dairy cows fed ethyl-cellulose rumen-protected methionine - Lam Phuoc Thanh; Nithat Wichasit; Yu Li; Fernanda Batistel; Wandee Tartrakoon; Claudia Parys; Jessie Guyader; Juan J. Loor (Journal of Dairy Science, 2023)
ABSTRACT: Skeletal muscle turnover helps support the physiological needs of dairy cows during the transition into lactation. We evaluated effects of feeding ethyl-cellulose rumen-protected methionine (RPM) during the periparturient period on abundance of proteins associated with transport AA and glucose, protein turnover, metabolism, and antioxidant pathways in skeletal muscle. Sixty multiparous Holstein cows were used in a block design and assigned to a control or RPM diet from −28 to 60 d in milk. The RPM was fed at a rate of 0.09% or 0.10% of dry matter intake (DMI) during the prepartal and postpartal periods to achieve a target Lys:Met ratio in the metabolizable protein of ∼2.8:1. Muscle biopsies from the hind leg of 10 clinically healthy cows per diet collected at −21, 1, and 21 d relative to calving were used for western blotting of 38 target proteins. Statistical analysis was performed using the PROC MIXED statement of SAS version 9.4 (SAS Institute Inc.) with cow as random effect, whereas diet, time, and diet × time were the fixed effects. Diet × time tended to affect prepartum DMI, with RPM cows consuming 15.2 kg/d and controls 14.6 kg/d. However, diet had no effect on postpartum DMI (17.2 and 17.1 ± 0.4 kg/d for control and RPM, respectively). Milk yield during the first 30 d in milk was also not affected by diet (38.1 and 37.5 ± 1.9 kg/d for control and RPM, respectively). Diet or time did not affect the abundance of several AA transporters or the insulin-induced glucose transporter (SLC2A4). Among evaluated proteins, feeding RPM led to lower overall abundance of proteins associated with protein synthesis (phosphorylated EEF2, phosphorylated RPS6KB1), mTOR activation (RRAGA), proteasome degradation (UBA1), cellular stress responses (HSP70, phosphorylated MAPK3, phosphorylated EIF2A, ERK1/2), antioxidant response (GPX3), and de novo synthesis of phospholipids (PEMT). Regardless of diet, there was an increase in the abundance of the active form of the master regulator of protein synthesis phosphorylated MTOR and the growth-factor-induced serine/threonine kinase phosphorylated AKT1 and PIK3C3, whereas the abundance of a negative regulator of translation (phosphorylated EEF2K) decreased over time. Compared with d 1 after calving and regardless of diet, the abundance of proteins associated with endoplasmic reticulum stress (XBP1 spliced), cell growth and survival (phosphorylated MAPK3), inflammation (transcription factor p65), antioxidant responses (KEAP1), and circadian regulation (CLOCK, PER2) of oxidative metabolism was upregulated at d 21 relative to parturition. These responses coupled with the upregulation of transporters for Lys, Arg, and His (SLC7A1) and glutamate/aspartate (SLC1A3) over time were suggestive of dynamic adaptations in cellular functions. Overall, management approaches that could take advantage of this physiological plasticity may help cows make a smoother transition into lactation.